The inside out forehand as a tactical pattern in men`s professional tennis - Martin-Lorente, E.; Campos, J.; Crespo, M. (International Journal of Performance Analysis in Sport, 2017)
The so-called inside out forehand has an active role in the baseline strategy because it offers the players new possibilities of hitting the incoming ball with their preferred shot by covering their weaker side and, at the same time, playing the ball with more open angles and directions which create more aggressive patterns of play. The purpose of this study is to analyse the use of this shot as well as its incidence on the men`s professional game both, right- and left-handed players. Eighteen matches corresponding to Grand Slam and ATP finals played between 2011 and 2014 were analysed. Eleven players (men) with ATP rankings between 1 and 14 were studied. Data show that the inside out forehand is used as a tactical weapon to counter the shots directed to the left-hand side zone of the court. The use of the inside out forehand has multiple consequences and, especially, the relationship between the use of the inside out forehand and the impact zone since it has been shown that as the player moves away laterally from the centre of the court, the percentage of transition shots is reduced, while the percentage of winners and errors increases.